Vigor Benih Mangga Kweni (Mangifera Odorata Griff) Dari Calon Pohon Indukan Yang Berbeda Di Desa Ipi Dan Desa Bente Kecamatan Bungku Tengah Kabupaten Morowali - Nurfiana Abdan; Maemunah Maemunah; Adrianton Adrianton (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
ABSTRACT This study aimed at obtaining high vigor of Kweni mango seeds. It was conducted in April to July 2017, at the Laboratory of Seed Technology and Academic Gardens of the Agriculture Faculty of Tadulako University, Palu.  It was carried out in two stages: the viability testing using a completely randomized design (RAL) in which the seeds were taken from different sources i.e. Ipi 1, Ipi 14 and Bente 8; and the vigor testing using a randomized block design (RAK) in which the seeds were grouped based on the height of the parent tree sources. At each stage of the experiment there were three treatments with six replicates.  The results of this study indicated that the seeds coming from the Ipi 1 source grew well under the viability and vigor tests, and it had the highest vigor.  Keyword : Mango, source of seed, viability, vigor.